Targeted therapies for vascular malformations - Kane, Gavin; Fernandez-Pineda, Israel (Frontiers in Medicine, 2024)
Targeted medical therapies for the treatment of vascular malformations is an exciting and evolving area of research. As the identification of specific causative genetic mutations involved in vascular malformations becomes more accessible and inexpensive, the development of targeted therapies to address these genetic anomalies becomes all the more enticing. It is an excellent example of the potential of translational research where basic science discoveries are translated to clinical practise from ‘bench to bedside’. In this mini-review we aim to synopsise some of the recent studies published in this area with specific focus on the paediatric population. We also aim to highlight the growing demand for future research in the field to elucidate further the optimum duration of treatments, strategies for discontinuation, potential for combination of therapies and the effects of prolonged use of these medications.